Politeness in law tutorials - Pillai, Stefanie (Journal of Modern Languages, 2017)
In view of the above, the following research questions are examined in this study: How did the tutor deal with instances when she did not get an answer to her question? How was politeness manifested or inherent in the way the tutor dealt with instances when she did not get an answer to her question? How do (I) and (2) relate to the concept of an adjacency pair?